Pengalaman dan Peran Remaja dalam Meningkatkan Kesehatan Masyarakat: Literature Review - Cahyaningrum, Erma; Yulian, Vinami (Prosiding Seminar Nasional Keperawatan Universitas Muhammadiyah Surakarta, 2023)
Health cadres in the community are very important in assisting and monitoring public health, health cadres are the right target as a place in implementing health programs because as the first referral place for health services, to increase community empowerment it is necessary to involve all elements, namely youth. Adolescents are also part of society who have the right to live healthy and are obliged to maintain and improve individual and community health. Adolescents with a lot of potential and skills are obliged to play an active role as pioneers, drivers, and executors of health development. The method in this literature review is to collect relevant journals obtained on the Community Service Journals, Pudmed, Google Scholar databases with a period of 2019 to 2023 (5 years). The results of the conclusions based on the results of the review that has been carried out can be concluded that the experience and role of adolescents in improving health in the community has not been carried out much, and has not focused on conducting training for every youth in an area.